Conceptualizing money creation as a ḥabs in debt market - Belabes, Abderrazak (Journal of Islamic Economics Lariba, 2024)
IntroductionMonetary creation is one of the major weak points of the in-depth analysis of economic life. The literature on Islamic economics, Islamic finance, and the jurisprudence of contemporary financial transactions is no exception to this rule. The reason is that money is reduced to its functionalist dimensions as a simple means of exchange, and considered a secondary issue with regard to the prohibition of ribāʿ.ObjectivesThis research proposes a new theoretical framework that conceptualizes money creation as a ḥabs in debt market. This conceptual framework makes it possible to avoid subjecting economic life to the system of monetary creation withholded, in debt and to nourish the illusion of economic growth boosted by debt.MethodThe study is based on genealogical method, which strives to trace the origins of things, and fundamentally takes its source from ancient literature on ansāb (lineage), al-awāʿil (things done for the first time), and long history, starting from the question: Where does it come from? It is a question of linking the phenomenon of ḥabs to its source, which is the building of the Kaʿaba by Ādam as the original ḥabs on earth.ResultsThe first significant result is that ḥabs is a general phenomenon that applies to a range of things. The waqf is only one of a number of possible forms. The second result is that reading the meaning of the word ḥabs allows us to link the various forms of withhold to the origin of life on earth when God ordered Adam to live on earth, then to build the Kaʿaba. The third result is the proposal of a new analytical framework for economic life which considers monetary creation as a ḥabs in debt market. ImplicationsThis study shows that ḥabs is an original conceptual tool which must be fully integrated into the analysis of economic life to broaden perspectives, promote understanding, and open new paths to action, in terms of social and economic policy, to build more resilient societies, while improving quality of life.Originality/Novelty This result provides a conceptualization of monetary creation on an unprecedented approach of ḥabs in debt market, and constitutes a basis for the development of policies, that move away from false economic growth boosted by debt, towards modes of existence based on voluntary cooperation, participative administration in community affairs, and the primacy of social purpose over capital.